Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa di SMP Negeri 2 Kuok - Elmi Sapitri; Zulfah Zulfah; Astuti Astuti; Zulhendri Zulhendri; Adityawarman Hidayat (Griya Journal of Mathematics Education and Application, 2026)
This study aims to investigate the effect of the cooperative learning models Teams Games Tournament (TGT) on the mathematical problem-solving abilities of seventh-grade student at SMP Negeri 2 Kuok. The background of this research stems from students low ability to solve mathematical problems that require logical and systematic thinking. This study employed a quasi-experimental method with a nonequivalent control group design. The research subjects consistend of two classes: the experimental class, which was tought using the TGT model, and the control class, which was taught using conventional methods. The results showed a significant difference in mathematical problem-solving abilities between students taught using the TGT model and those taught using conventional methods. Additionally, there was a significant improvement in students, problem-solving skills after implementing the TGT model. Therefore, the TGT learning model is effective in enchancing students’ mathematical problem-solving abilities.